Exploring facilitation in virtual simulation in nursing education: A scoping review - Lena Günterberg Heyn; Espen Andreas Brembo; Kirsten Røland Byermoen; Caroline Cruaud; Hilde Eide; Jill Flo; Anita Nordsteien; Grith Overgaard; Hugrun Ösp Egilsdottir (PEC Innovation, 2023)
Objective: To systematically map existing research regarding the reflective feedback in virtual simulation in undergraduate nursing education. Methods: A scoping review was conducted based on the Arksey and O'Malley framework and the PRISMA-ScR. Results: We included 41 studies from 15 different countries. The simulation interventions allowed for interaction between the student and the virtual patient, the software, faculty, peers, or a combination of two or more of these. Students valued reflective feedback during and after the simulation. Conclusions: Our review emphasizes the importance of a human in the loop. Feedback before, during, and after the simulation is possible in virtual simulation where the facilitator can pause the virtual scenario and stimulate reflections during the simulation to obtain deep learning. Virtual simulation provides opportunities to give feedback from the software, such as cues or direct feedback. Innovation: There is a lack of focus on the feedback process and there is a need to revitalize the role of facilitators in a virtual simulation to determine their relative contribution in this process. Several studies reported the usefulness or the effect of virtual simulation on learning processes, but most lacked emphasis on investigating the significance of including a human in the loop.